The Liability for Damage in the Commercial Law - Podojilová, Petra; Kalinová, Miluše, 1952-; Hásová, Jiřina, 1954-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2010)
The bachelor thesis deals with problems of the liability for damage in the commercial law. The main aim of this thesis is to provide well-arranged and consistent information about the liability for damage in the Czech commercial law. At the beginning there is the definition of the liability and in the following part there is the explanation of the liability for damage according to the Civil Code and Commercial Code. This part of the thesis includes both the general and the special legal regulations.The practical part of the thesis includes three judical decisions. These decisions help to understand how courts work and adjudicate in practice.
Vedoucí práce: Miluše Kalinová
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Způsob přístupu: Internet
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2010
Rok obhajoby 2010
Keywords: podnikání a právo [obor bakal. práce]; bakalářské práce; bachelor's theses